Targeting autophagy to overcome drug resistance in cancer therapy. (August 2015) - Kumar, Ankit; Singh, Umesh Kumar; Chaudhary, Anurag
Autophagy, a catabolic process, is activated by conditions of stress and nutrient deprivation, which occurs to maintain metabolic homeostasis by performing catabolic lysis of excessive or unnecessary proteins, and injured or aged organelles. Autophagy is regulated by various signaling pathways. Main regulators of autophagy are the PI3K–Akt–mTOR pathway, Beclin1, Bcl-2, Ras and p53. Autophagy plays dual role in cancer, shows both tumor suppressive and oncogenic activity. It is accepted that drug resistance in cancer cells can be overcome by inhibition of autophagy. Herein, we summarize autophagy as a potential target of anticancer drugs and targeting autophagy provides a promising therapeutic strategy to circumvent resistance and enhance the effect of anticancer therapies for cancer patients.